Philosophical Examination Of Nature's Gifts In The Works Of Mahmud Al-Zamakhshari - Yunusovich, Adilov Zafar (Pubmedia Social Sciences and Humanities, 2024)
This article analyzes nature and its blessings in the works of Mahmud al-Zamakhshari (d. 1144), a renowned Islamic scholar and theologian best known for his contributions to Arabic grammar, rhetoric, and tafsir (Quranic exegesis). Al-Zamakhshari’s treatment of nature is deeply rooted in his belief in the signs of God’s power and wisdom embedded in the world. The paper examines how his works reveal a holistic view of nature, not only as a physical phenomenon but as a divine manifestation that serves as a medium for spiritual reflection and moral guidance.